Lingual ortodonti - Mihri Amasyali; Tancan Uysal (Cumhuriyet University, 2011)
Currently, aesthetics of the anterior teeth is a significant issue in general dentistry and the most frequently cited reason for patients seeking orthodontic treatment. For many years, lingual orthodontics was perceived as complex and problematic treatment procedures and therefore not widely used internationally. However, during the last decade, the percentage of patients treated with lingual orthodontics has increased, appliance systems have renewed, and the technique has developed to such an extent that in some cases, it is easier, quicker, and more accurate than traditional buccal orthodontics. The aim of this review is to evaluate and generally consider the usage of lingual orthodontics which commonly preferred by patients in routine orthodontic procedures and look through current applications. Additionally, special considerations regarding the contemporary diagnosis and treatment planning in lingual orthodontics are presented in this study. ÖZET Günümüzde, ön dişlerin estetik olarak dizilimi ve görünümü genel diş hekimliğinde önemli bir konu olmuş ve bu önem hastalar için lingual ortodonti tercihinde birinci sebep halini almıştır. Lingual ortodonti yıllardır karmaşık ve uygulanması zor tedavi yöntemlerinden kabul edilmiş ve uluslar arası alanda yaygın bir kullanım alanı bulamamıştır. Ancak son dönemlerde, bu yöntem aracılığıyla tedavi edilen hasta yüzdesi artmış, vakalarda uygulanan aygıtlar yenilenmiş, tedaviler kolaylaştırılmış, hızlandırılmış ve her geçen gün geleneksel ortodontik tedavilerle elde edilen başarılara ulaşılmaya başlanmıştır. Bu derlemenin amacı, ortodontide her geçen gün daha fazla hastanın tercih ettiği bu uygulamayı genel olarak değerlendirmek ve güncel uygulamalara genel bir bakış yapmaktır. Ayrıca lingual ortodontik uygulamalardaki güncel muayene ve tedavi planlamalarından, karşılaşılan özel durumlardan da bu çalışmada bahsedilecektir. Anahtar Kelimeler: Lingual ortodonti, güncel uygulamalar